The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21203/rs.3.rs-127171/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Lung Involvement in COVID-19 Pneumonia Based on Ultrasound Images

Abstract: Background: Lung ultrasound (LUS) can be an important imaging tool for the diagnosis and assessment of lung involvement. Ultrasound sonograms have been confirmed to illustrate damage to a person’s lungs, which means that the correct classification and scoring of a patient’s sonogram can be used to assess lung involvement.Methods: The purpose of this study was to establish a lung involvement assessment model based on deep learning. A novel multimodal channel and receptive field attention network combined with R… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…(5) Several studies have shown that LUS can detect interstitial disease, subpleural consolidations, and respiratory distress of any aetiology, with sensitivity and specificity superior to chest radiography and comparable to CT. (6)(7)(8) Indeed, LUS has already been recommended in past viral pandemics (9) and growing evidence demonstrates its effectiveness in patients with COVID-19, (10) which allows identifying the degree of lung involvement, its course, and the possible association between the initial lung involvement and its prognosis. (11)(12)(13)(14)(15) Our objective was to evaluate the performance of LUS through the lung ultrasound score (LUS score) to determine the severity of pneumonia and the short-term outcomes of patients with COVID-19 admitted to the intensive care unit. We hypothesize that the Lung Ultrasound Score (LUS) correlates with clinical evolution and predicts mortality in critically ill COVID-19 pneumonia patients.…”
Section: Introductionmentioning
confidence: 99%
“…(5) Several studies have shown that LUS can detect interstitial disease, subpleural consolidations, and respiratory distress of any aetiology, with sensitivity and specificity superior to chest radiography and comparable to CT. (6)(7)(8) Indeed, LUS has already been recommended in past viral pandemics (9) and growing evidence demonstrates its effectiveness in patients with COVID-19, (10) which allows identifying the degree of lung involvement, its course, and the possible association between the initial lung involvement and its prognosis. (11)(12)(13)(14)(15) Our objective was to evaluate the performance of LUS through the lung ultrasound score (LUS score) to determine the severity of pneumonia and the short-term outcomes of patients with COVID-19 admitted to the intensive care unit. We hypothesize that the Lung Ultrasound Score (LUS) correlates with clinical evolution and predicts mortality in critically ill COVID-19 pneumonia patients.…”
Section: Introductionmentioning
confidence: 99%